Decision-Making Process in Advanced Cancer Patients Regarding Communicating Information About Their Disease to Their Minor Children - Imanishi, Yuko; Akimoto, Noriko (Journal of Japanese Society of Cancer Nursing, 2024)
Our purpose was to clarify the decision-making process in advanced cancer patients regarding communicating information about their disease to their minor children, and to obtain suggestions for nursing practice.Semi-structured interviews were conducted with 20 patients diagnosed with advanced cancer who had children aged 6 to under 18 years old at the time of diagnosis of advanced cancer, were told by their doctors that they were not eligible for curative treatment, and were undergoing treatment or watchful waiting to prolong life or relieve symptoms, and in whom the period between diagnosis of advanced cancer and the interview was 15 years or less. The modified grounded theory approach was used.The decision-making process in advanced cancer patients regarding communicating information about their disease to their children is divided into three core categories: (1)“choosing whether or not to communicate information about their disease to their children based on their own values,” (2)“communicating after thinking about when, from whom, and in what way to communicate,” and (3)“being unable to decide whether or not to communicate about death.” “Checking with a trusted person if they made a good decision” supports the process of (2).The following approaches by nurses were suggested to support patients' decision-making: listening to advanced cancer patients’ thoughts and feelings that led to their decision of whether or not to communicate their disease information to their minor children; providing continued support for the decision-making process, which consists of the three core categories predicted to be followed by patients; respecting and supporting the patients’ timing of communicating the information about their disease to their children; and facilitating the patients’ narratives about difficulties of communicating about death and listening to them carefully so that they can reconstruct their own narrative and come to their own conclusions about whether or not to communicate about their death to their children.